Virtual Worlds: Relationship Between Real Life and Experience in Second Life - Anstadt, Scott P.; Bradley, Shannon; Burnette, Ashley; Medley, Lesley L. (International Review of Research in Open and Distributed Learning, 2013)
Due to the unique applications of virtual reality in many modern contexts, Second Life (SL) offers inimitable opportunities for research and exploration and experiential learning as part of a distance learning curriculum assignment. A review of current research regarding SL examined real world social influences in online interactions and what the effects on users may be. This aids students in understanding the social constructionist perceptions and worldview of those persons they may serve in social services. This suggests the importance of developing an understanding of the relationship between users’ real life (RL) and their SL. Some research has begun to reveal the effectiveness of telecommunication and computer simulation with certain clients in the fields of mental health and social work, yet there is a lack of sufficient research done within the context of virtual worlds. The current study surveyed users of several educationally and health focused SIMS (simulations) as to what motivates their SL and RL interactions. The data explores associations between users’ RL and their SL in several areas,potentially addressing the future role of educating social work students regarding research methodology in online virtual reality interactions. Implications for social work are discussed including engaging clients using incentives for social participation built into the SL milieu.